Recurrent odontogenic keratocyst in patient with Gorlin-Goltz Syndrome - Gutiérrez Patiño-Paul, Alejandro (2020)
Gorlin-Goltz syndrome (GGS) is an autosomal dominant disorder characterized by skeletal abnormalities, multi- ple Keratocysts Odontogenic (KCOs) and basal cell carcinoma. Comparative studies of the associated KCOs and those not associated with the GGS have been performed, and the presence of a greater number of satellite cysts, solid proliferations of the epithelium, inﬂammations, calciﬁcations, more intense mitotic activity of the epithelial cells, and greater recurrence of the KCOs associated with the GGS. The purpose of this case report is to provide an objective basis for the therapeutic management of KCOs in patients with GGS and a review of the scientiﬁc literature. We present the case of a 63-year-old patient, with a history of GGS, who underwent multiple surgical interventions, including exeresis of KCOs in both jaws, who came to the consultation, nine years after her last intervention, for an Odontostomatological check-up, ﬁnding KCO recurrent in upper right maxilla, performing enucleation, peripheral ostectomy and application of carnoy solution.